Constitutional law and criminal justice - Roberson, Cliff, 1937- (New York : Routledge, 2022)
"Illuminating US constitutional concepts in plain language and clarifying nuances in the law, this third edition of Constitutional Law and Criminal Justice simplifies understanding of the United States judicial system for those without advanced legal training. It updates recent decisions by the Supreme Court of the United States and includes a discussion on the current makeup and policy of the Supreme Court. Learning objectives and summary outlines of recent Supreme Court decisions, combined with practical examples and selected actual court documents, enhance students' understanding of the most important issues regarding the US Constitution and its application in the criminal justice system. The book begins with an overview of the Bill of Rights, followed by an examination of the components of the judiciary. It moves on to a discussion of due process; the First, Fourth, Fifth, Sixth, and Eighth Amendments; and the exclusionary rule. A unique chapter addressing civil liability and the criminal justice professional is especially relevant to students in criminal justice programs. Concise and informative, this book is designed to be used in undergraduate courses in criminal justice and justice administration programs in universities and community colleges"--
U.S. Constitution -- The concept of due process -- Fourth Amendment -- Fourth Ammendment issues -- Exclusionary rule -- Fifth Amendment issues -- Sixth Amendment issues -- Eight Amendment -- First Amendment -- Civil liability -- Writ of Habeas Corpus.
OCLC-licensed vendor bibliographic record.
Keywords: Constitutional law -- United States; Criminal justice, Administration of -- United States; Criminal procedure -- United States; Civil rights -- United States; SOCIAL SCIENCE / Criminology